Influence of Spray Technology and Application Rate on Leaf Deposit and Ground Losses in Mountain Viticulture - Costas Michael (Agriculture, 2020)
Leaf deposit and ground losses generated from spray application in mountain viticulture were evaluated. Four treatments were examined: A spray gun (1000 L ha−1, High-Volume Sprayer—HVS), a motorized knapsack sprayer (200 L ha−1, Low Volume Sprayer—LVS), and a conventional orchard mist blower calibrated at 500 L ha−1 (OS500) or 250 L ha−1 (OS250). The four treatments were assessed using the same tank concentration of tracer in two training systems: a trellis and a goblet. Sprayer treatment, vine side, and vine height significantly affected leaf deposit (p < 0.05). The absolute amount of leaf deposit increased with application volume, but when the amount of deposit was standardized to 1 kg ha−1, LVS resulted in the highest deposit, followed by HVS, OS250, and OS500. Deposition for the goblet system was ca. half that for the trellised vineyard. Ground losses standardized to 1 kg of tracer ha−1 were twice as high for HVS than for LVS, and four times as high for HVS than for OS250 and OS500, in both training systems. The current work suggests that low volume applications in vineyards are a viable and more environmentally friendly alternative than high volume treatments.